Methods Of Organizing Individual Work with Young Specialists in Preschool Educational Organizations - Karimova Umida Sharifovna (Genius Publishing Group, 2024)
This article describes in detail the methods of organizing individual work with young specialists in preschool educational organizations
Keywords: management method; communication; socio-psychological